Lecture summaries - MacKie, E W; Pitts, Lynn F; Whyte, Ian D (Proceedings of the Society of Antiquaries of Scotland, 1984)
Three lecture summaries: Excavations at the Broch of Leckie, Stirlingshire Roman legionary fortresses as exemplified by Inchtuthil Scottish agriculture in the 17th century: continuity and change